2022
DOI: 10.1111/apt.17239
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial: effects of gluten‐free diet on symptoms and the gut microenvironment in irritable bowel syndrome

Abstract: Background: A gluten-free diet reduces symptoms in some patients with irritable bowel syndrome (IBS) through unclear mechanisms.Aims: To assess the effects of gluten-free versus gluten-containing diet on symptoms and the gut microenvironment, and to identify predictors of response to the glutenfree diet in IBS Methods: Twenty patients with IBS and 18 healthy controls (HC) followed a glutenfree diet during two 14-day intervention periods where they sprinkled either gluten (14 g/day) or rice flour powder over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…IBS being a heterogenous condition and important molecular determinants were not included. One previous study identified response to a gluten free diet versus a gluten-containing diet, but that study was underpowered for such a sub-analysis of differential response (Algera et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IBS being a heterogenous condition and important molecular determinants were not included. One previous study identified response to a gluten free diet versus a gluten-containing diet, but that study was underpowered for such a sub-analysis of differential response (Algera et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning gluten, one clinical trial with a gluten-free diet versus a gluten-containing diet reported that response to the gluten-free diet could be predicted by the metabolite profile at baseline, identification of metabolites was not presented. However, the study was underpowered (Algera et al, 2022 ). To date, there are no generally accepted recommendations for tailored nutritional advice in IBS (Bennet et al, 2020 ; Drossman, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Fitzpatrick and Halmos for their interest in our randomised controlled trial on the effects of gluten‐free diet (GFD) on symptoms and the gut environment in irritable bowel syndrome (IBS) 1,2 . Based on this study, no strong clinical recommendations are made regarding the GFD in IBS, and we agree that gut microbial patterns are exciting as a predictor for response to diet therapy.…”
mentioning
confidence: 96%
“…Objective markers for gluten‐associated symptoms are lacking. Algera and colleagues have attempted to provide a biomarker of symptoms in response to gluten in patients with IBS through analysis of faecal microbiota and metabolite profiles in patients with IBS administered gluten and rice (placebo) powder on a background gluten‐free diet 1 . Despite no overall difference in symptom scores between gluten and placebo, microbiota and metabolites profiles differed in six of 20 IBS subjects, who responded solely to gluten provocation compared to the other 14 subjects.…”
mentioning
confidence: 99%